Mukwahepo : women soldier mother - Namhila, Ellen Ndeshi (UPCC book collections on Project MUSE., 2013)
In 1963 Mukwahepo left her home in Namibia and followed her fiance across the border into Angola. They survived hunger and war and eventually made their way to Tanzania. There, Mukwahepo became the first woman to undergo military training with SWAPO. For nine years she was the only woman in SWAPO's Kongwa camp. She was then thrust into a more traditional women's role - taking care of children in the SWAPO camps in Zambia and Angola. At Independence, Mukwahepo returned to Namibia with five children. One by one their parents came to reclaim them, until she was left alone. Already in her fifties,